Policies on renewable energy at the European and national level of governance: Assessing policy adaptation in the Czech Republic - Gamze Tanil; Petr Jurek (Energy Reports, 2020)
The European Union defined itself as a global leader in the promotion and development of renewable energy sources. The European Union initiated crucial changes in renewable energy policies in its Member States. This paper presents the results of a comprehensive analysis of policy debate and policy outputs adopted by the European Union and by the Czech Republic over a fourteen-year period (2004-2018). We investigate how the Czech Republic's domestic policy on renewable energy sources has reacted to EU-level policy norms, strategies and institutional developments. There are different theories used to explain differentiated processes of Europeanization of domestic structures. One of them, the institutionalist approach reveals how the European Union effect is filtered and mediated through pre-existing domestic institutions, rules, norms and political cultures. We demonstrate that Czech policy makers implemented crucial EU-level policy norms to the national legislative framework, but these norms have not been fully internalized by political actors and society. Thus, the promotion of renewable energy sources in the Czech Republic can be considered as a direct effect of policy development at the EU level, not as output of autonomous Czech policy debate. It poses certain risk for the future development of renewable energy sources policy support.
Keywords: 330; Czech republic; Europeanization; Legislative adaptation; Normative adaptation; Renewable energy policy